PENGARUH PERILAKU NASABAH BANK SAMPAH TERHADAP PENGELOLAAN SAMPAH DI TPA BAKUNCI KABUPATEN TANAH LAUT - Mariatul Kiptiah; Meldayannoor Meldayannoor; Anton Kuswoyo (EnviroScienteae, 2019)
Trash Bank is effective management which aims to encourage people in managing a better environment. The trash bank increased people's awareness in reducing trash transported to the landfill, as well as being an effective solution in dealing with the trash so that through the community trash bank they could deposit trash and increased their wealth as a collective income, and to be able to process trash into compost. This study aimed to determine the behavior of the community in managing their trash, to influence public awareness in the uses of trash in Bakunci Landfill trash bank as a means to increase people's income and to reduce trash; which is processed into compost; as an environmental feasibility analysis. The method used in this study was a survey method with purposive sampling as its sampling technique. The obtained research data were in the form of primary and secondary data. The results of this study were: the behavior of garbage bank customers; including simple administration and a good operational system; influenced Y in the form of savings and was influenced by variable X1, namely the administration and variable X2, namely Operational. Both of these variables had a significant effect of 92.29% with an error tolerance of 0.05 or 5%. The influence of trash bank customers in managing trash into compost had an effect on the income of trash bank customers with a profit of Rp. 23,856,000 / month and was also feasible for the environment.